Interleukin-7 signalling defects in naive CD4+ T cells of HIV patients with CD4+ T-cell deficiency onantiretroviral therapy are associated with T-cell activation and senescence - Tanaskovic, S.; Fernandez, S.; Price, Patricia; French, M. (Lippincott Williams and Wilkins, 2014)
Objective: To examine the relationship of defects in interleukin (IL)-7-induced naive CD4+ T-cell homeostasis with residual immune activation and CD4+ T-cell senescence in HIV patients receiving antiretroviral therapy (ART) who exhibit persistent CD4+ T-cell deficiency. Design: IL-7 induced proliferation of, and IL-7 receptor signalling in, total and naive CD4+ T cells of HIV patients who had low (<350 cells/µl) or normal (>500 cells/µl) CD4+ T-cell counts on ART was examined and related to markers of CD4+ T-cell activation and senescence and innate immune activation. Methods: Total, naive (CD45RA+ CD27+) and CD31+ naive CD4+ T cells from aviremic HIV patients (n = 39) with nadir CD4+ T-cell counts less than 100 cells/µl, who had received ART for a median time of 7 (range 1–11) years, were assessed for CD127 expression, proliferation (Ki67), signal transducer and activator of transcription 5 phosphorylation (pSTAT5) and CD127 modulation following IL-7 stimulation. Changes were related to proportions of CD4+ T cells expressing HLA-DR or CD57 and plasma levels of sCD14, CXCL9 and CXCL10.Results: Patients with CD4+ T-cell deficiency exhibited lower expression of CD127 on total, naive and CD31+ naive CD4+ T cells. Downregulation of CD127 after culture with IL-7 correlated inversely with CD4+ T-cell counts and directly with Ki67 expression. Induction of pSTAT5 in CD4+ T-cell subsets was greater in patients with normal CD4+ T-cell counts. CD127 expression correlated inversely with proportions of CD4+CD57+ T cells, and pSTAT5 induction correlated inversely with CD4+ T-cell expression of HLA-DR and CD57. Conclusion: Defects of IL-7 signalling in HIV patients with persistent CD4+ T-cell deficiency receiving ART are associated with CD4+ T-cell activation and senescence.